Pertanggungjawaban Pidana Pelaku Tindak Pidana Kerusuhan di Stadion Kanjuruhan - Mufti, Muhammad Wildan (Jurnal Hukum Statuta, 2023)
As social beings, humans require interaction and cooperation with others to live their lives. Conflicts arising from differing interests necessitate law as a guide for behavior and protection of individual rights within society. This research employs a normative legal research method with a normative juridical approach to explain the legal phenomena related to Law No. 11 of 2022 on Sports. A qualitative method is used, focusing on document and literature studies to explore the fundamental concepts underlying human behavior patterns in the legal context. The criminal responsibility of perpetrators of criminal acts at Kanjuruhan Stadium includes the improper use of tear gas, which caused many deaths and injuries, as well as human rights violations. This issue needs to be addressed through fair law enforcement and good coordination among all relevant parties. The Kanjuruhan tragedy raises serious questions about criminal liability for human rights violations and the use of tear gas in the stadium, emphasizing the need for punishment that is commensurate with the wrongdoing and the maintenance of human rights principles in every step of law enforcement.